The effects of milk and yogurt consumption on the anthropometric measurements of adolescents - Öztürk, Meryem Elif; Yabanci Ayhan, Nurcan (Progress in Nutrition, 2020)
Milk consumption during adolescence is associated with growth, but the relationship between consumption of milk and BMI is currently discussed. The aim of this study is to determine the relationship between consumption of milk and yogurt and the anthropometric measurements of adolescents. This study was conducted with 544 adolescents who were 14-17 years old. Their milk and yogurt consumption frequencies and amounts were obtained, and their anthropometric measurements were recorded. Milk consumption alone was associated with height (p<0.05), but not BMI (p>0.05). Total milk and yogurt consumption were associated with height and weight (p<0.05), but not BMI (p>0.05). Milk and yoghurt consumption support growth, but are not related with obesity.